Свобода в пределах атеизма: в защиту автономности самосознания в философии Александра Кожева - ДОРОФЕЕВ, Яков Станиславович (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2025)
The article explores the features of the relationship between human self-consciousness and freedom within the philosophical-anthropological concept of a French neoHegelian thinker Alexandre Kojève. Special attention is given to the critical reevaluation of the thesis asserting their fundamental incompatibility, which challengesKojève’s position on the autonomy of a subject in the context of the asymmetrical master-slave relation. The derivation of fundamental heteronomy from mediation by the Other as the sole possible condition for the emergence of self-consciousness is argued to be epistemologically flawed, as the pursuit of pure, unconditional, and absolute freedom within causal determinism is inherently antinomic, whereas humanexistence outside causality is fundamentally impossible. The author undertakes a consistent defense of the autonomous status of self-consciousness through dialectical, phenomenological, and existential lenses.